The relation of education to agriculture - Hulse, Fred (My University, 1893)
Introduction: This subject embraces two words that include more in extension and intention than any other two in our language and they are subject to more degrees of proficiency. The one, education, may be subdivided in several ways, but the classification I wish to use is into a general and special. Also, I desire to use the same division with agriculture. But, before so subdividing, I would like to very briefly notice the history of each.
Citation: Hulse, Fred. The relation of education to agriculture. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Education; Agriculture; History; Theses; Manuscripts (documents)